iii) a2 – 62 – c2 – 2ab – 2bc – 2ac if expression is a=2, b=-2, c=1​

Question

iii) a2 – 62 – c2 – 2ab – 2bc – 2ac if expression is a=2, b=-2, c=1​

in progress 0
Aaliyah 2 months 2021-08-01T09:51:05+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-08-01T09:52:13+00:00

    \large{\colorbox{black}{\underline{\underline{\bf{\orange{☆• Be Brainly •☆}}}}}}

    a^2 – 6^2 – c^2 – 2ab – 2ac

    2^2 + 36 – 1^2 – ( 2 × 2 × 2 ) – ( 2 × 2 × 1 )

    4 + 36 + 1 – 8 – 4

    41 – 12

    29

Leave an answer

Browse

9:3-3+1x3-4:2 = ? ( )